A Dead Man’s Contract: P. BM EA 10077 Revisited - Baetens, Gert (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
Reedition of P. BM EA 10077, a unique mummification contract from Ptolemaic Thebes, rejecting earlier interpretations linking the document with the provision of embalming materials and the seventy-day mummification period.